Avaliação da eficácia do uso da pele da tilápia (Orechromis Niloticus) liofilizada como curativo biológico em queimaduras de II grau superficial: estudo clínico, randomizado e controlado - Silva, Diana Carla Pereira da (2023)
Burns are essentially injuries to the skin and tissues that can originate from different factors, including thermal, chemical, electrical, friction or radiation, reaching a certain extent of the body surface, also causing partial or total destruction of adjacent tissues. The objective of this research was to evaluate the effectiveness of using freeze-dried tilapia skin as a biological dressing in the treatment of superficial second-degree burns in adults compared to occlusive dressing with silver foam. A Phase II, prospective, open, monocentric, randomized, pilot study was carried out with a sample of 24 patients randomly treated with lyophilized Nile Tilapia skin (n=12) and silver foam (n=12). Regarding the patients treated with the dressing with freeze-dried Nile Tilapia skin, the average number of days of treatment (11.5±0.52) was lower than that of patients treated with silver foam (11.83± 0.39). As for the report of pain during dressing change, both groups had pain greater than 5 on the visual analogue scale. After changing the dressing, 83.33% of patients treated with Nile Tilapia skin reported a decrease in pain-related events, compared to 58.33% of those treated with silver foam. It was also found that in 83.33% of the cases of patients treated with freeze-dried Nile Tilapia skin, there was no need to replace any dressing while for the silver foam, in 100% of the cases, there was at least least one replacement. The number of analgesics above 01 tablet used in the treatment with lyophilized Nile Tilapia skin was 41.67% compared to 66.67% in the treatment with silver foam. However, for all evaluated outcomes, there was no statistically significant difference between both groups. Thus, based on the research, it can be concluded that freeze-dried Nile Tilapia skin is effective as an occlusive biological dressing.